2006
DOI: 10.1001/archpsyc.63.12.1377
|View full text |Cite
|
Sign up to set email alerts
|

Use of Latent Profile Analysis to Identify Eating Disorder Phenotypes in an Adult Australian Twin Cohort

Abstract: Lifetime weight ranges and the severity of eating disorder symptoms affected clustering more than the type of eating disorder symptom.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
105
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 106 publications
(117 citation statements)
references
References 38 publications
(35 reference statements)
12
105
0
Order By: Relevance
“…To achieve this, we take a ''cross-disorder'' approach and explore what endophenotypes might exist that cross the boundaries between currently conceptualized disorders. This approach is consistent with some observations including a latent profile analysis that suggested, from a general population perspective, there is no meaningful differentiation between clinically significant eating disorders, including EDNOS 33 and with unpublished data which show AN and BN spectrum disorders share 50% of their genetic risk factors (Wade, Treloar, Heath, Martin, unpublished manuscript). It is also noteworthy that this approach may identify trans-diagnostic endophenotypes that may identify meaningful biological bridges between entire classes of psychiatric illnesses (e.g.…”
Section: Cross-disorder Perspectivesupporting
confidence: 88%
See 3 more Smart Citations
“…To achieve this, we take a ''cross-disorder'' approach and explore what endophenotypes might exist that cross the boundaries between currently conceptualized disorders. This approach is consistent with some observations including a latent profile analysis that suggested, from a general population perspective, there is no meaningful differentiation between clinically significant eating disorders, including EDNOS 33 and with unpublished data which show AN and BN spectrum disorders share 50% of their genetic risk factors (Wade, Treloar, Heath, Martin, unpublished manuscript). It is also noteworthy that this approach may identify trans-diagnostic endophenotypes that may identify meaningful biological bridges between entire classes of psychiatric illnesses (e.g.…”
Section: Cross-disorder Perspectivesupporting
confidence: 88%
“…[77][78][79] A composite measure of weight concern was elevated in women with AN compared to controls, as was dietary restraint for women who had either lifetime AN or BN. 33 Consistent with evidence supporting this variable as an endophenotype, a follow-up study of 108 infants at 8 years of age showed that maternal restraint predicted worries about being too fat in girls but not boys. 80 However, the composite measure of weight concern has been found to be influenced by environmental variance only, 81 while other studies suggest that measures of body dissatisfaction, weight preoccupation and drive for thinness are influenced by genetic factors in older adolescent female twins.…”
Section: Cognitive Featuresmentioning
confidence: 77%
See 2 more Smart Citations
“…12 LPA has the advantage of allowing for the inclusion of continuous indicators while LCA is limited to categorical indicators. To date, this empirical classification research has been limited to adult samples, [13][14][15][16][17][18][19][20] with the exception of one recent report combining adolescents and young adults. 21 In adult samples, this research has demonstrated that LCA/LPA reliably identify clinically meaningful subgroups of individuals with eating disorders including those that resemble AN, BN, and one particular type of EDNOS characterized by binge eating without purging (binge eating disorder [BED]).…”
Section: Introductionmentioning
confidence: 99%